Audel electrical course for apprentices and journeymen - Rosenberg, Paul (Wiley, 2004)
Spend your study time wiselyAs you advance from student to apprentice to journeyman status, you log a lot of study hours. Make the most of those hours with this fully updated, sharply focused self-study course. It contains everything you need to know about electrical theory and applications, clearly defined and logically organized, with illustrations for clarity and review questions at the end of each chapter to help you test your knowledge.* Understand electron theory and how electricity affects matter * Recognize applications for both alternating and direct current* Compr.